Metabolic Response of Black Tiger Shrimp (Penaeus monodon) to Acute Ammonia Nitrogen Stress - Yangyang Ding; Shigui Jiang; Song Jiang; Yundong Li; Qibin Yang; Lishi Yang; Jianhua Huang; Jianzhi Shi; Pengying Li; Hongshan Diao; Falin Zhou (Biology)
High concentrations of ammonia nitrogen could result in the death of aquatic animals and cause a huge economic loss in the aquaculture industry. However, the metabolic responses to acute ammonia nitrogen stress remain largely unknown in Penaeus monodon. In this study, we first investigated the histological change in tissues in Penaeus monodon under 96 h acute ammonia nitrogen stress. The result of the paraffin section showed that acute ammonia nitrogen stress induced severe epithelial detachment and lumen dilatation of the hepatopancreas, swollen and hemocyte infiltration of the gills, and mucosa exfoliation and shortened villi of the intestine in Penaeus monodon, suggesting the impairment of the normal physiological function in these tissues. We next examined the change in the metabolic product in the plasma and the enzyme activity in the hepatopancreas after ammonia nitrogen stress. Upon ammonia stress, both the concentration of ammonia and urea nitrogen significantly increased, while there was no significant increase in the concentration of uric acid, which is consistent with the results that the enzyme activity of glutamine synthetase (GS), glutamate dehydrogenase (GDH), and aspartate transaminase (GOT) became significantly elevated and the enzyme activity of adenosine deaminase (ADA) in the purine metabolism pathway significantly decreased after ammonia stress, suggesting that shrimp could convert excessive ammonia to urea for ammonia detoxification through the ammonia–nitrogen metabolism pathways. Interestingly, we also observed a significant increase in superoxide dismutase (SOD) activity, suggesting a potential role of this antioxidant enzyme in the clearance of reactive oxygen species (ROS) induced via ammonia stress. Moreover, we found that acute ammonia nitrogen stress inhibited the enzyme activity of caspase 3 and caspase 8, suggesting an important role of apoptosis in protecting Penaeus monodon against acute ammonia stress. Overall, our findings revealed that Penaeus monodon may employ metabolic and purine pathways and undergo oxidative stress and apoptosis for ammonia detoxification under ammonia nitrogen stress, thus providing new insight into the metabolic response of shrimp to acute ammonia stress.